Innovations in insuring the poor: Index-based livestock insurance in Mongolia - Mahul, Olivier; Belete, Nathan; Goodland, Andrew (International Food Policy Research Institute, 2009)
The Mongolian rural economy is based on livestock reared by semi-nomadic herders. Agriculture contributes around 20 percent of the country’s gross domestic product, and herding accounts for more than 80 percent of agriculture. According to the 2008 livestock census, Mongolia has about 44 million head of livestock, consisting of goats, sheep, cattle, yaks, horses, and camels. Livestock provide sustenance, income, and wealth to nearly half the residents of Mongolia. Shocks to the well-being of livestock therefore have devastating implications for the rural poor and for the overall Mongolian economy. Major shocks are common because Mongolia has a harsh climate where animals are herded with limited shelter. From 2000 to 2002, harsh winters (dzud) killed 11 million animals. The Government of Mongolia has struggled with the obvious question of how to address this problem. Managing risk in the livestock sector requires a combination of risk mitigation and financial approaches. Pastoral risk mitigation, including winter shelters, fodder crop storage, and improved management of winter pastures, can help herders better prepare for moderate weather events. In extreme dzud events—that is, sudden-onset winter storms with very low temperatures, high winds, and heavy snow—high levels of livestock mortality are often unavoidable. Pastoral and herd management must therefore be complemented by financial mechanisms that provide herder households with immediate liquidity after a disaster. In 2001 the Government of Mongolia requested assistance from the World Bank to address the problem of frequent high death rates in the livestock population. Traditional indemnitybased livestock insurance (based on individual losses) has proved ineffective in Mongolia because of the high cost of covering animals spread across vast areas, ex ante moral hazard (herders failed to protect their livestock), and ex post moral hazard (herders falsely reported animal deaths). The World Bank recommended an index-based insurance program based on livestock mortality rates by species and soum (county), as well as a comprehensive riskfinancing strategy including self-insurance by herders, market-based insurance, and a social safety net. Index-based insurance can lower administrative costs and reduce moral hazard and adverse selection. Its main disadvantage is the presence of basis risk—that is, the index payout may not exactly match the individual livestock loss.